Factors associated with cervical cancer screening participation among migrant women in Europe - Marques, Patrícia (2020)
Background: Cervical cancer screening has been effective in reducing incidence and mortality of cervical cancer, leading European countries to implement screening programs. However, migrant women show lower screening participation compared to nationals. This scoping review aims to provide a synthesis of the growing evidence on factors associated with participation in cervical cancer screening among migrant women in Europe. Methods: Electronic peer-reviewed databases were searched in November 2019 for studies on factors related to the participation of migrants in cervical cancer screening conducted in EU/EFTA countries, using comprehensive search expressions. Retrieved articles were screened and those eligible were selected for data extraction. Quantitative and qualitative studies were included. Factors were classified in barriers and facilitators and were divided into further categories. Results: Twenty out of 96 articles were selected and analyzed. Factors associated with participation in cervical cancer screening were classified in categories related to sociodemographic, healthcare-system, psychological, migration, knowledge, language, and cultural factors. Lack of information, lack of female healthcare providers, poor language skills, and emotional responses to the test (especially fear, embarrassment and discomfort) were the most reported barriers to cervical cancer screening. Encouragement from healthcare providers and information available in migrants' languages were frequently stated as facilitators. Results on the role of sociodemographic factors, such as age, education, employment and marital status, are the most conflicting, highlighting the complexity of the issue and the possibility of interactions between factors, resulting in different effects on cervical cancer screening participation among migrant women. Several identified barriers to screening are like those to access to healthcare services in general. Conclusions: Efforts to increase migrant women's participation in CCS must target barriers to access to healthcare services in general but also specific barriers, including cultural differences about sexuality and gender, past traumatic personal experiences, and the gender and competences of healthcare professionals performing CCS. Healthcare services should strengthen resources to meet migrants' needs, including having CCS information translated and culturally adapted, as well as healthcare providers with skills to deal with cultural background. These findings can contribute to improve CCS programs among migrant women, reducing health disparities and enhancing their overall health and well-being.